Vida e Facebook : um estudo das práticas de produção e compartilhamento de conteúdo no Facebook - Silva, Cláudia Moreira de Jesus (2017)
Life is surrounded by the internet, by reactions and situations built and mediated by websites that encourage the group relationship and the collective development through the sharing of content, expressed as images, sounds, videos and what else creativity generates and the cyberspace allows. Present times are marked by the convergence of means of communication, integrating many medias in mobile devices that are getting evermore versatile and accessible. This convergence helps the creation of a collective and simultaneous involvement for people talk in real time about what they see with their friends, family, and colleagues, all part of these virtual networks, making it possible for ideas and values to circulate in real time. Chatting between people and virtual groups instigate the development of actions aimed at the production of content, the collaborative work and sharing. This process promotes the construction of the new and a collective force centered on the union of interests, expertise and exchanges. In short, this immediate and synergistic communicative process, especially the sharing process, must be followed and understood. In this study, therefore, we seek to identify the practices of production and sharing of content on Facebook and the relationship of this practice with the daily experience of young high school students. We cite as an example the relationship between producing and sharing, their meanings, circumstances, thematic and main influences. The research was developed in schools in the cities of Cuiabá and Várzea Grande and other municipalities near Cuiabá